Using innovative techlologies in project method Of teaching kazakh and russian (Eurasian Journal of Philology Science and Education, 2018)
This article discusses using innovative techlologies in project method of teaching Kazakh and Russian as foreign languages. This article provides various guidelines, corresponding to different stages of training. For the formation of various speech training skills offered interactive forms. The system of exercises presented in this article contributes to the development of oral communication. Teaching – a complex and multi-pronged process. The activities of the teacher should be aimed to maximize the learning process. Accounting for these moments allows the teacher to build a class methodically competently, to adjust their pace, alternate forms of work, that means to intensify the activities of the students. Communicative principle, which became the base for most of didactic concepts and successfully implemented in almost all stages of education, largely strengthened ties methodology and linguistics, increased interest in teaching communicative process parameters. In the article, various methodic recommendations are provided, which correspond to various stages of education. It is given attention not only to linguistic form of expression, but to informal form. Interactive forms of teaching are proposed for speaking. System of exercises, provided in the article, contributes to development of oral communicative.